ANALISIS TEORI AL-UQUD AL-MURAKKABAH (KONTRAK HYBRID) - Muhammad Rasyid Ridlo (Taksasila Edukasi Insani, 2023)
This research is an analytical study of Hybrid Contracts or Multi-Akad which still creates ambiguity in the community regarding the types, laws, and provisions in practice in the field. The purpose of this research is to be able to answer the Multi Akad theory so that the practice in the field can be in accordance with the existing theory. This research approach uses descriptive qualitative methods with library research techniques